Efek Pemberian Fraksi Etil Asetat Ekstrak Etanol Kulit Buah Jeruk Bali (Citrus Maxima Merr) terhadap Kadar Glukosa Darah Tikus Hiperglikemia - Desita, Maya; Roy Indrianto Bangar Siagian; Astriani Natalia Br Ginting (JOURNAL SAINS STUDENT RESEARCH, 2025)
Diabetes Mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels (hyperglycemia). Herbal medicine is often used as an alternative treatment, and pomelo peel (Citrus maximaMerr) is believed to have potential as an antihyperglycemic agent due to its content of bioactive compounds such as flavonoids and vitamin C. This study aimed to examine the antihyperglycemic effect of the ethyl acetate fraction of the ethanol extract of pomelo peel (Citrus maxima Merr) in alloxan-induced Wistar rats. Hyperglycemic rats were divided into 6 groups (Normal Control, Negative Control, Positive Control/Metformin, and Fraction Doses of 125, 250, 500 mg/kgBW). The treatment was administered for 14 days. The results showed that the pomelo peel ethyl acetate fraction significantly reduced the blood glucose levels of the hyperglycemic rats, with the effect becoming clearly visible by Day 9. This reduction effect was dose-dependent, where the 500 mg/kgBW dose provided the most optimal antihyperglycemic effect, closely approaching the effect of Metformin and the normal group. The ethyl acetate fraction ofpomelo peelis effective in lowering the blood glucose levels of hyperglycemic rats. This activity is strongly suspected to originate from the content of active compounds such as flavonoids, saponins, and alkaloids.